Antioxidant and Antibacterial Activities of Noni Fruit (Morinda Citrifolia) Extract - Fitriana, Wiwit Denny; Fajril Islami, Mohamad (Jurnal Kimia Riset, 2025)
Noni fruit (Morinda citrifolia), also known as noni, is widely used in Indonesia for its antioxidant and antibacterial benefits. This study evaluated the antioxidant and antibacterial activities of ethanol-extracted Noni fruit. Antioxidant activity was assessed using the DPPH method, showing an IC50 value of 28.82 μg/mL. Antibacterial activity was tested using the Resazurin Microtiter Assay (REMA), revealing MIC values against Bacillus subtilis (2.5 mg/mL), Staphylococcus aureus (10 mg/mL), Salmonella typhi (10 mg/mL), Pseudomonas aeruginosa (>10 mg/mL), and Propionibacterium acnes (0.63 mg/mL). The results indicate that Noni fruit extract has potential as a natural source of antioxidants and antibacterials.